Determination of HLA Class I Antigens in some Iraqi patients with Acute and Chronic Urticaria - H. AL-Mousawi, Mayida (Iraqi Journal of Science, 2023)
This research was included (60) patients diagnosed as having Urticaria, (30) patients with acute Urticaria and (30) patients with chronic Urticaria in addition to ( 30) healthy people were chosen as a control. lymphoid cells (Lymphocytes) isolated from patients and healthy controls and added to Terasaki Plates which containing specific antibodies to the( HLA -Class I Antigen) to identify alleles of these antigens. The result showed (HLA-A2) allele increased in its recurrences in patients with acute Urticaria and significantly higher when compared with chronic Urticaria patients and control group, which have Relative Risk (RR) (4.12 , 13.50), respectively, and raise the value of the Etiological Fraction (EF) to (0.45 , 0.55), respectively, also significantly higher when compared acute and chronic Urticaria patients with the control group associated with the Relative Risk (6.88) and the Etiological Fraction (0.37) to explain the presence of Positive Association between the disease and (HLA-A2) allele, which gives genetically predisposed to infection of Urticaria